2020
DOI: 10.3390/ijms21249414
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Synthetic Cannabinoids JWH-122, JWH-210, UR-144 in Oral Fluid of Consumers by GC-MS and Quantification of Parent Compounds and Metabolites by UHPLC-MS/MS

Abstract: The consumption of synthetic cannabinoids (SCs) has significantly increased in the last decade and the analysis of SCs and their metabolites in human specimens is gaining interest in clinical and forensic toxicology. A pilot study has been carried out using a combination of an initial last generation gas chromatography-mass spectrometry (GC-MS) screening method for the determination of JWH-122, JWH-210, UR-144) in oral fluid (OF) of consumers and an ultra-high performance liquid chromatography high resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…OF was collected with Salivette ® tubes (Barcelona, Spain) to determine the concentrations of UR-144 and THC at baseline, 10, 20 and 40 min, and 1, 2, 3 and 4 h after self-administration. Samples were centrifuged and frozen at −20 °C until posterior analysis by a modified and validated liquid chromatography-mass spectrometry method to quantify THC and UR-144, but permitting detection of metabolites (LC-MS/MS) [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…OF was collected with Salivette ® tubes (Barcelona, Spain) to determine the concentrations of UR-144 and THC at baseline, 10, 20 and 40 min, and 1, 2, 3 and 4 h after self-administration. Samples were centrifuged and frozen at −20 °C until posterior analysis by a modified and validated liquid chromatography-mass spectrometry method to quantify THC and UR-144, but permitting detection of metabolites (LC-MS/MS) [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…UR-144 cardiovascular effects were slightly higher than those induced by JWH-210, but JWH-210 subjective effects were higher. When compared to 20 mg THC, all three SCs induced less intense cardiovascular and subjective effects ( La Maida et al, 2020 ). JWH-210 results are in agreement with the marked but transient cardiovascular and euphoric effects described following the controlled administration by inhalation of JWH-018, one of the most studied compounds of the JWH family ( Theunissen et al, 2018 ; Toennes et al, 2018 ; Theunissen et al, 2019 ; Theunissen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a rise in the recreational use of extremely potent SCs such as JWH-122 and JWH-210 has been reported ( La Maida et al, 2020 ). To date, the recreational use of JWH-122 and/or JWH-210 has been analytically documented in several cases of driving under the influence (DUI) and nonfatal and fatal cases ( Yeakel and Logan, 2013 ; Dziadosz et al, 2014 ; Musshoff et al, 2014 ; Tuv et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…As reported above, the second most commonly consumed class of NPSs is synthetic cannabinoids, which similar to that reported for synthetic cathinones, create health concerns due to their severe adverse events and enhanced toxicity [ 9 ]. Whereas several analytical methods can detect these compounds in cases of acute and fatal intoxications [ 10 ], information about the disposition of synthetic cannabinoids and their metabolites in consumers’ biological matrices is still scarce.…”
mentioning
confidence: 99%
“…For the first time, La Maida et al identified and quantified JWH-122, JWH-210, UR-144, and their principal metabolites in the oral fluid of consumers [ 10 ]. A combination of an initial last-generation gas chromatography–mass spectrometry (GC-MS) screening method for the determination of the parent compounds in oral fluid and an ultrahigh-performance liquid chromatography–high-resolution mass spectrometry (UHPLC-HRMS) confirmatory method for the quantification of JWH-122, JWH-210, UR-144, and their metabolites was set up and validated for this purpose.…”
mentioning
confidence: 99%